Aqueous Voltammetry in the Near Absence of Electrolyte. Issue 60 (6th October 2017) - Li, Xiuting; Batchelor‐McAuley, Christopher; Laborda, Eduardo; Compton, Richard G.
Abstract: In order to minimize the incidence of the CO2 hydrolysis and conduct aqueous electrochemistry in the virtual absence of electrolyte, a novel methodology is developed to achieve the near minimum conductivity (≈60 nS cm −1 ) for an aqueous solution through in situ deionization with ion exchange resin beads. Aqueous electrochemistry studying the oxidations of platinum, ferrocenemethanol, and hydrogen (H2 ) were conducted in the near complete absence of trace ionic species at a platinum microelectrode ( d =10 μm). Both surface and solution phase electrochemical reactions were clearly observed, indicating that under these conditions there is a sufficiently compressed double layer for an interfacial electron transfer to be driven and the iR effects are significantly smaller than theoretically expected. Abstract : Minimalist : The near minimum conductivity (≈60 nS cm −1 ) for an aqueous solution is achieved through in situ deionization with ion exchange resin beads. The feasibility of electrochemical reaction in aqueous media in the near absence of the supporting electrolyte is demonstrated.